Q: When x equals 0 y equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x = y = 0 ?

6

x-y=0 x=y so you will use that in the other equation by substituting every y with x 2x+y=0 2x+x=0 3x=0 x=0/3 x=0 then use that in the previous equation by substituting every x with 0 x=y 0=y; y=0 finally x=0 and y=0

y = 6

y = x2 + x = 0 x (X + 1) = 0 x = 0 is one solution x = -1 is the other

Related questions

x = y = 0 ?

If: 3x+y = 4 and x+y = 0 Then: x = 2 and y = -2

6

x-y=0 x=y so you will use that in the other equation by substituting every y with x 2x+y=0 2x+x=0 3x=0 x=0/3 x=0 then use that in the previous equation by substituting every x with 0 x=y 0=y; y=0 finally x=0 and y=0

y = 6

y = x2 + x = 0 x (X + 1) = 0 x = 0 is one solution x = -1 is the other

8

y = x + 0

solve for y so if x + y = 0 then y = -x

The domain is the x values, so x = 0 to 10. The range is the y values, so y = 0 to 25.

The period is the length of x over which the equation repeats itself. In this case, y=sin x delivers y=0 at x=0 at a gradient of 1. y next equals 0 when x equals pi, but at this point the gradient is minus 1. y next equals 0 when x equals 2pi, and at this point the gradient is 1 again. Therefore the period of y=sinx is 2pi.

x+y=245 x=0-245 y=0-245